Development of Social Studies Teaching Materials Based on Religious Moderation Values in Islamic Elementary School - Sanusi, Sanusi; Ahsani, Eva Luthfi Fakhru (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2024)
The importance of introducing insight into religious moderation from an early age, especially at the age level of Elementary School (SD) or Madradsah Ibtidaiyah (MI) through the development of social studies teaching materials that are integrated with the values of moderation is a necessity to maintain and care for diversity which is increasingly eroding. Implicitly, the spirit of moderation in religion has indeed been shown in several materials and teaching materials at the elementary school level, even though they are still in a very simple form. This research design is Research and Development (R&D) or Research and Development. The sample technique used is the sample technique aimed at conducting research, namely MI NU Miftahul Falah Dawe Kudus. Data collection techniques using test techniques, interviews, documentation and questionnaires. The results of research on the development of IPS teaching materials based on religious moderation values were developed using the Thiagarajan research and development method, namely the Four-D (4-D) development model consisting of define, design, develop, and disseminate. IPS teaching materials based on moderation values with the theme of the beauty of togetherness are effective in improving student learning outcomes. Based on the results of the two average similarity tests on improving students' cognitive learning outcomes, it shows that the experimental class has a higher increase in cognitive learning outcomes than the control class.